Testicular involvement of Brucellosis: A 10-year, multicentre study - Mehmet Celik; Fethiye Akgul; Sevil Alkan; Deniz Altındag; Fatih Esmer; Ahmet Sahin; Davut Ipek; Yeliz Cicek; Esra Gurbuz; Mehmet Resat Ceylan; Nevin Guler Dincer (Journal of Infection in Developing Countries)
Introduction: The genito-urinary system is one of the most common areas of involvement in brucellosis. To present the epidemiological, clinical, and laboratory characteristics of patients with testicular involvement associated with brucellosis, together with the diagnostic and therapeutic approaches.